Advantages of using insulation with lower thermal conductivity versus WT 2021 – comparison of the costs of materials, buying and operating a heating device, and a carbon footprint generated - Zawiska, Patrycja (Budownictwo i Architektura / Civil and Architectural Engineering, 2026)
This article presents a comparative analysis of the use of standard insulation material compliant with the current Technical Conditions WT 2021, compared to insulation material with improved thermal conductivity parameters on building partitions. The information collected shows the impact on construction costs and the facility's carbon footprint during operation for the two solutions analysed. The main objective of the study was to identify the differences between the two options and to evaluate the cost-effectiveness of choosing the most advantageous result in economic and environmental terms, i.e. insulation material with optimal thermal conductivity parameters. For research purposes, information on a completed architectural project was used. This is a single-family house in which the recommended thermal insulation with optimal thickness and thermal conductivity parameters was used. The study enabled calculating the pay-back period and comparing CO2 emissions over ten years. The data presented, showing the benefits of choosing a sustainable solution, can serve as recommendations for the design of new buildings, but also represent potential for the thermal modernisation of existing architectural facilities.